Pengembangan Bahan Ajar Handout Berbasis Kearifan Lokal “Tais Mollo” Pada Materi Bangun Datar Untuk Meningkatkan Hasil Belajar Matematika Kelas V SD Inpres Sanam - Olla, Yufita; Koli, Radka Bodkova; Hano, Alvin Javier (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low mathematics learning outcomes on plane geometry among elementary school students indicate the need for contextual teaching materials that are relevant to students’ learning characteristics and local environment. This study aimed to develop a handout-based teaching material integrating the local wisdom of Tais Mollo to improve the mathematics learning outcomes of fifth-grade elementary school students. The study employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of the define, design, develop, and disseminate stages. The research subjects were 20 fifth-grade students of SD Inpres Sanam. Data were collected through expert validation sheets, teacher and student response questionnaires, and pretest–posttest achievement tests. Descriptive statistics were used to determine the validity and practicality of the developed product, while its effectiveness was analyzed using a paired-samples t-test and normalized gain (N-Gain). The results showed that the handout achieved a very valid category based on material expert validation (86.25%), media expert validation (92.50%), and language expert validation (82.50%). The developed product was also considered highly practical, with a teacher response score of 85.90% and positive responses from students during the implementation. Furthermore, the paired-samples t-test revealed a statistically significant improvement in students’ mathematics learning outcomes (p < .001). The mean score increased from 52.25 in the pretest to 76.00 in the posttest, with an N-Gain score of 0.7065, indicating a high improvement category. These findings demonstrate that the Tais Mollo local wisdom-based handout is valid, practical, and effective in supporting contextual mathematics learning and improving elementary students’ understanding of plane geometry concepts